2005
DOI: 10.1128/jcm.43.9.4659-4664.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Caliciviruses Detected in Sporadic and Outbreak Cases of Gastroenteritis in France from December 1998 to February 2004

Abstract: We compiled sequence and epidemiological data from 172 caliciviruses detected in France from December 1998 to February 2004 in sporadic and outbreak cases. The results showed a cocirculation of strains with a majority of genogroup II (GII) noroviruses. Three groups of noroviruses, not detected before in our laboratory, emerged and spread during the period: the recombinant GGIIb and Norwalk-related strains not amplified in the polymerase gene in 2000 and a new Lordsdale variant in 2002. We observed that (i) GII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
65
0
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 31 publications
4
65
0
8
Order By: Relevance
“…In our convenience sample, outbreaks in childcare settings were less frequently caused by GII.4 (and more frequently by GI) strains than hospital and nursing home outbreaks, which corresponds to a recent publication that reported a higher frequency of GII.4 strains in outbreaks in healthcare settings than in outbreaks involving younger persons [5]. Findings from France suggest that GII noroviruses are more common in sporadic cases whereas GI strains are predominant in outbreaks in children [33].…”
Section: Discussionmentioning
confidence: 47%
“…In our convenience sample, outbreaks in childcare settings were less frequently caused by GII.4 (and more frequently by GI) strains than hospital and nursing home outbreaks, which corresponds to a recent publication that reported a higher frequency of GII.4 strains in outbreaks in healthcare settings than in outbreaks involving younger persons [5]. Findings from France suggest that GII noroviruses are more common in sporadic cases whereas GI strains are predominant in outbreaks in children [33].…”
Section: Discussionmentioning
confidence: 47%
“…In this study, the highest rates of GGIIb detection were observed in January-February 2002 and the fall and winter of [2003][2004]. These periods coincide with GGIIb adult outbreaks in France [41]. So, the rate of detection of GGIIb and GGII.4 norovirus strains identified in children are similar to those circulating in the adult population in the same period.…”
Section: Discussionmentioning
confidence: 55%
“…Este hallazgo ha sido comunicado también en otros trabajos, en que alrededor de 40 a 50% de los casos permanecen sin un diagnóstico causal 40,42 . La falta de diagnóstico etiológico de diarreas es frecuente, de ahí la importancia de incorporar técnicas diagnósticas más sensibles ya que los tests de rutina generalmente resultan negativos 2,7,8 . La detección de NoV es difícil debido a la gran variabilidad genética que dificulta el diagnóstico de laboratorio de rutina; la técnica de ELISA tiene una baja sensibilidad que obliga a una confirmación de un resultado negativo por métodos moleculares 32,41,43 .…”
Section: Discussionunclassified
“…La introducción del diagnóstico empleando RPC en tiempo real ha sido de gran importancia para mejorar el diagnóstico y establecer el rol relevante de NoV en brotes epidémicos agudos y en casos esporádicos de diarrea. Este método diagnóstico ha permitido demostrar la amplia heterogeneidad y rápida evolución de las variantes genéticas de NoV 8,9,[11][12][13][14][15] ; La diversidad antigénica y la falta de sistema de cultivo in vitro del virus mantendrá al diagnóstico molecular como el mejor método de detección de NoV. La RPC a tiempo real ha emergido como el estándar para el diagnóstico y detección de NoV, ya que combina un alto rendimiento, reproducibilidad, sensibilidad y especificidad 11,27,[42][43][44][45][46] . El 36,6% de los pacientes en este estudio fueron ingresados al hospital con un diagnóstico diferente al de una gastroenteritis, adquiriendo la infección probablemente en forma nosocomial (plazo de latencia para los síntomas de 3 o más días), siendo mayor para NoV (32,1%) que para RV (5,7%).…”
Section: Discussionunclassified
See 1 more Smart Citation